Methods and Equipment for Experimental Evaluation of the Performance of Shell and Hull Structures - Yu. G. Lyudmirsky; S. S. Assaulenko; A. V. Kramskoi (Advanced Engineering Research)
Introduction. Pressure-operated thick-walled hull structures are the most common type of high-duty welded structures. When these structures are loaded with internal pressure, a complex biaxial stress field arises in them, which is summed up with the fields of residual welding stresses. Therefore, when selecting a technology for manufacturing critical welded structures, the results obtained during conventional uniaxial tests of samples are insufficient. The variety of factors affecting the performance of structures, and the difficulties of separate assessment of their influence, caused the need to maximize the approximation of experimental conditions to the real working conditions of the structure.Materials and Methods. Testing of full-scale structures has a number of advantages, but they are extremely expensive, and, as a rule, only one, the weakest link, is identified, the bearing capacity of the other structural elements remains unclear. For testing, UDI radiometric installations designed for different sample sizes were used. The presented installations allow testing samples of various shapes, types of welded joints (butt, T-bar), changing the position of welded parts.Results. Without rejecting the results obtained during the testing of full-scale structures in the works of the Bauman Moscow State Technical University, DSTU, NRC «Kurchatov Institute» – CRISM «Prometey», and the authors proposed to conduct the basic scope of the research on individual structural elements that would reflect the characteristic features of loading, manufacturing technology, and operating conditions. The design of the «fitting-sheet» connections was applied, which made it possible to increase the indicators of the failure initiation and propagation to the level of the base metal.Discussion and Conclusions. Schemes of structures for obtaining a biaxial tension or bending field in samples were presented. Samples tested according to the proposed schemes allowed us to draw conclusions about the performance of welded joints under conditions close to the actual operation of the structures under study. The proposed test scheme is used by research laboratories in our country and around the world.